Severity of climacteric symptoms among Peruvian women from an urban coastal community and a rural Andean community - Renato Beas; Celeste Díaz-Pardavé Jose Arriola-Montenegro; Lorenzo D'Angelo; Adrian Riva-Moscoso; Piero Larco-Castilla (James Cook University, 2021)
Introduction: The aim of this study was to evaluate the severity of climacteric symptoms among two Peruvian communities, adjusted for sociodemographic and clinical variables in climacteric women. Methods: A cross-sectional study was conducted on 90 subjects from two different communities (an urban coastal and a rural Andean district from Peru). The Menopause Rating Scale was used to assess climacteric symptoms. Prevalence ratios with 95% confidence interval (PR 95%CI) were estimated using generalized linear Poisson models with family robust standard errors. Results: A higher probability of severe climacteric symptoms was found in women who were from the Andean community than those who were from the coastal one (PR 2.42, 95%CI 1.47-3.99; p=0.001), which remained in the adjusted model (RP 1.72, 95%CI 1.04-2.86; p=0.035). Conclusion: Understanding the variation of climacteric symptoms among geographically distinct communities could contribute to improving women's quality of life.